Grinding paste for hard alloy polishing and preparation method and application thereof
Oil-soluble abrasive paste residue and water-soluble abrasive paste are solved by using grinding paste with white petroleum or paraffin and fatty acids in cemented carbide polishing. The problem of excessive thermal energy achieves the authenticity and cleanliness of metallographic structures, meeting the requirements of metallographic observation.
Patent Information
- Application Number
- CN202411325074.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
When polishing existing cemented carbides, it is difficult for oil-soluble abrasive paste to completely remove residues, which affects the observation of metallographic microscopy. Water-soluble abrasive paste will cause excessive grinding heat energy and cause metallographic structure distortion.
Using oil-phase lubricants containing white petroleum jelly or paraffin and fatty acids, aqueous lubricants of solid polyethylene glycol and small molecule polyols, emulsifiers and polyvinylpyrrolidone grinding paste, through softening, lubricating, antioxidant and dispersing effects, Reduce grinding heat energy, prevent tissue from precipitation, and ensure the authenticity of metallographic structure.
Effectively avoid oily residue, reduce grinding heat energy, prevent metallographic structure distortion, and meet the authenticity and cleanliness requirements of metallographic observation.
Smart Images

Figure CN119193005A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cemented carbide polishing, and in particular relates to a grinding paste for cemented carbide polishing and a preparation method and application thereof. Background Art
[0002] Polishing the surface of metal samples is an important step in the microscopic analysis of metal materials. The purpose is to reveal the real internal structure of the metal sample. Polishing can remove the damage layer, scratches, pits and oxide layer produced when the metal sample surface is polished, so that the surface of the metal sample reaches a high degree of smoothness to reveal the real structure, which is crucial for the accuracy of the microscopic structure observation and analysis results of the metallographic microscope. Polishing media (abrasive paste) is an important material for the surface polishing of metal samples. Its cutting performance, lubrication performance, grinding heat energy, etc. and the degree of cleanliness after polishing will directly affect the microscopic resolution of the real structure of the metal sample.
[0003] The working principle of abrasive paste is to use abrasives to grind and polish the surface of metal samples. During the grinding and polishing process, friction and cutting occur between the abrasive and the metal sample. The abrasive particles will continuously contact, collide and roll with the surface of the metal sample to remove the raised parts of the metal sample surface, thereby improving the smoothness and finish of the metal sample surface, enhancing the corrosion resistance of the passivation film, and improving the appearance quality.
[0004] Abrasive pastes are classified into oil-soluble abrasive pastes and water-soluble abrasive pastes according to solvents. When oil-soluble abrasive pastes are used for polishing carbide specimens, the oily residues are difficult to completely remove. When the specimens are observed under a high-magnification metallographic microscope, the stubborn oily fine residues will seriously affect the resolution of the metal microstructure; and when water-soluble abrasive pastes are used for polishing carbide specimens, although the cleaning problem can be solved, due to the high grinding heat energy, the severe polishing heat will affect the carbide bonding structure, resulting in the occurrence of distortion phenomena such as the precipitation of metal bonding structure, thus affecting the metallographic observation requirements. Summary of the invention
[0005] The first object of the present invention is to provide an abrasive paste which can avoid oily residue and improve the authenticity of metallographic structure to meet the requirements of metallographic observation.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned abrasive paste.
[0007] The third object of the present invention is to provide the use of the above-mentioned grinding paste in cemented carbide polishing.
[0008] The grinding paste provided by the present invention contains abrasive, oil phase lubricant, water phase lubricant, emulsifier and polyvinyl pyrrolidone and optional dispersant in a mass ratio of 100:(300-1000):(300-1000):(100-600):(10-160):(0-300); the oil phase lubricant is white vaseline or a mixture of paraffin and / or fatty acid and white vaseline; the water phase lubricant is a mixture of solid polyethylene glycol and small molecule polyol.
[0009] The grinding paste provided by the present invention is prepared by compounding an abrasive with an oil phase lubricant, a water phase lubricant, an emulsifier, polyvinyl pyrrolidone and an optional dispersant, and using white vaseline or a mixture of paraffin and / or fatty acid and white vaseline as an oil phase lubricant, and using a mixture of solid polyethylene glycol and a small molecule polyol as a water phase lubricant. The obtained grinding paste can avoid oily residue and improve the authenticity of metallographic structure, thereby meeting the requirements of metallographic observation. The reasons are speculated to be: white vaseline can soften, lubricate and resist oxidation; white vaseline or the oil phase lubricant composed of white vaseline, paraffin and / or fatty acids can reduce friction, reduce wear, reduce grinding heat, prevent the occurrence of "coking" during grinding, protect the metal bonding structure from being precipitated during grinding, and at the same time have an antioxidant effect on the surface of the polished sample, reducing the distortion of the sample structure; small molecule polyols have strong solubility and low freezing point, which can soften, dissolve and resist freezing of lubricating main materials such as paraffin, fatty acids and polyethylene glycol, prevent the lubricating main materials from crystallizing and hardening again, increase the viscosity of the paste, promote the dispersion and fusion of the lubricating main materials and other additives, ensure the thermal stability of grinding and polishing, and avoid local overheating during grinding to cause "coking" and cause metallographic structure distortion; polyvinyl pyrrolidone has strong solubility and low freezing point, which can soften, dissolve and resist freezing of lubricating main materials such as paraffin, fatty acids and polyethylene glycol, prevent the lubricating main materials from crystallizing and hardening again, increase the viscosity of the paste, promote the dispersion and fusion of the lubricating main materials and other additives, ensure the thermal stability of grinding and polishing, and avoid local overheating during grinding to cause "coking" and distortion of the metallographic structure; polyvinyl pyrrolidone has strong solubility and low freezing point After hot dissolution, it has antifreeze effects of dispersion and anti-reprecipitation, and can control the recrystallization of oily greases such as paraffin to achieve particle size control. At the same time, the addition of polyvinyl pyrrolidone can improve the gloss and dispersibility of the paste, improve the thermal stability of the grinding process, and effectively avoid the occurrence of metallographic structure distortion. The cleaning effect of the water-phase lubricant containing solid polyethylene glycol is reflected in its good solubility, which can effectively clean the dirt and grease on the surface of the sample. The addition of polyethylene glycol can improve the decontamination ability of the grinding paste and reduce the residual grease on the surface of the polished sample to avoid affecting the metallographic observation. In addition, emulsifiers are usually rich in hydrophilic groups and lipophilic groups, which can improve the tension of the oil-water interface and help stabilize the grinding paste system, thereby promoting the uniform mixing of the oil-phase lubricant and the water-phase lubricant, so that the mixed grinding paste has the comprehensive advantages of oil and water, thereby avoiding the metallographic distortion of the sample caused by the difficulty in cleaning the oily residue and the thermal instability of grinding.
[0010] In a preferred embodiment, the abrasive is diamond powder with a particle size of 0.5-2.5 microns. At this time, the abrasive has high hardness, good chemical stability and low wear rate, and can provide high-precision cutting and polishing effects during the grinding process. The ultrafine abrasive can grind the polished object to an extremely fine particle size, ensuring that the polished cemented carbide can reveal the most real structure without being damaged by cutting, and can more effectively avoid the occurrence of metallographic structure distortion such as cutting damage and scratches.
[0011] In a preferred embodiment, the emulsifier is a mixture of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters and oleic acid. In this case, the metallographic structure distortion phenomenon can be more effectively improved to meet the metallographic observation requirements. The reason is speculated to be that: mono- and di-glycerol fatty acid esters and sorbitol fatty acid esters are rich in lipophilic long-chain alkyl and hydrophilic hydroxyl groups, which can improve the surface tension of oil and water, control and stabilize the crystallization of oil, improve plasticity and ductility, prevent oil separation and stratification, make the fat particles fine and uniform, and thus promote the uniform mixing of incompatible bodies; oleic acid has hydrophilic groups and lipophilic groups, which can achieve mutual stability between oil and water, and play an emulsifying effect of oil hydrolysis, thereby completely removing oily residues and stabilizing grinding heat, avoiding the occurrence of sample metallographic distortion.
[0012] In a preferred embodiment, the grinding paste also contains a dispersant, and the dispersant is a mixture of liquid polyethylene glycol, polyvinyl alcohol and pure water, which can more effectively reduce the distortion of the sample surface tissue. It is speculated that the reason may be due to: the specific surface area of the nano diamond (abrasive) is large, the specific surface energy is high, it is in a thermodynamically unstable state, and the dispersion stability in the medium is poor and it is easy to reunite, so that the uneven paste of the abrasive is cut unevenly during the grinding and polishing process and produces tissue distortion. Polyvinyl alcohol dissolves in water to form a suspension that can be used as a nano diamond carrier, and the liquid polyethylene glycol has a moderate viscosity and can form a protective film on the diamond surface, effectively preventing the diamond powder from aggregating again.
[0013] The preparation method of the grinding paste provided by the invention comprises uniformly mixing abrasive, oil phase lubricant, water phase lubricant, emulsifier, polyvinyl pyrrolidone and optional dispersant. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a microscopic metallographic effect diagram of the surface of the cemented carbide before polishing with the grinding paste obtained in Example 1;
[0015] Figure 2 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 1;
[0016] Figure 3 This is a microscopic metallographic effect diagram of the surface of the cemented carbide before polishing with the grinding paste obtained in Example 2;
[0017] Figure 4 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 2;
[0018] Figure 5 This is a microscopic metallographic effect diagram of the surface of the cemented carbide before polishing with the grinding paste obtained in Example 3;
[0019] Figure 6 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 3;
[0020] Figure 7 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 4;
[0021] Figure 8 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 5;
[0022] Fig. 9 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 6;
[0023] Fig.10 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 7;
[0024] Fig.11 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Example 8;
[0025] Fig.12 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after being polished with the grinding paste obtained in Comparative Example 1;
[0026] Fig.13 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after polishing with the grinding paste obtained in Comparative Example 2;
[0027] Fig.14 This is a microscopic metallographic effect diagram of the surface of the cemented carbide after polishing with the grinding paste obtained in Comparative Example 3. DETAILED DESCRIPTION
[0028] The grinding paste provided by the present invention contains abrasive, oil phase lubricant, water phase lubricant, emulsifier, polyvinyl pyrrolidone and optional dispersant; the oil phase lubricant is white vaseline or a mixture of paraffin and / or fatty acid and white vaseline; the water phase lubricant is a mixture of solid polyethylene glycol and small molecule polyol. The mass ratio of the abrasive, oil phase lubricant, water phase lubricant, emulsifier, polyvinyl pyrrolidone and optional dispersant is 100:(300-1000):(300-1000):(100-600):(10-160):(0-300). Specifically, based on 100 parts by weight of the abrasive, the contents of the oil phase lubricant and the water phase lubricant are each independently 300-1000 parts by weight, such as 300, 400, 500, 600, 700, 800, 900, 1000 parts by weight or any value therebetween; the content of the emulsifier is 100-600 parts by weight, such as 100, 200, 300, 400, 500, 600 parts by weight or any value therebetween; the content of the polyvinyl pyrrolidone is 10-160 parts by weight, such as 10, 30, 50, 80, 100, 120, 140, 160 parts by weight or any value therebetween; the content of the dispersant is 0-300 parts by weight, such as 0, 10, 20, 50, 80, 100, 200, 300 parts by weight or any value therebetween.
[0029] In a preferred embodiment, the content of the abrasive is 5-10 parts by weight (such as 5, 6, 8, 10 parts by weight or any value therebetween), the content of the oil phase lubricant is 30-50 parts by weight (such as 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50 parts by weight or any value therebetween), the content of the water phase lubricant is 30-50 parts by weight (such as 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50 parts by weight or any value therebetween), and the content of the emulsifier is 10-30 parts by weight ( The content of polyvinyl pyrrolidone is 1-8 parts by weight (such as 1, 2, 4, 6, 8 parts by weight or any value therebetween), and the content of dispersant is 5-15 parts by weight (such as 5, 8, 10, 12, 15 parts by weight or any value therebetween). At this time, the components can achieve the best synergistic effect, which can effectively ensure that the surface of the cemented carbide is free of scratches, oily residues, and tissue distortion, and meet the requirements of microscopic metallographic observation.
[0030] In the present invention, the abrasive can be diamond powder, aluminum oxide powder, silicon oxide powder, silicon carbide powder, boronized nitrogen powder, steel sand powder, etc., and is particularly preferably diamond powder. The particle size of the diamond powder is preferably 0.5-2.5 microns, more preferably 0.5-1.5 microns, such as 0.5, 0.8, 1, 1.2, 1.5 microns or any value therebetween. Using the diamond powder of the above preferred particle size as an abrasive can ensure high-precision cutting and polishing effects during the grinding process, can better ensure that the cemented carbide structure is not damaged by cutting, and is more conducive to the exposure of the real structure of the cemented carbide after polishing.
[0031] In the present invention, oil phase lubricant is a mixture of white vaseline or paraffin and / or fatty acid and white vaseline, preferably a mixture of paraffin and / or fatty acid and white vaseline. When oil phase lubricant is a mixture of paraffin and / or fatty acid and white vaseline, it is more conducive to the stability of grinding heat energy, so that metallographic structure authenticity is more truly fed back, and now, the mass ratio of the total content of paraffin and fatty acid to white vaseline content in oil phase lubricant is preferably (2-3): 1, such as 2: 1, 2.2: 1, 2.4: 1, 2.6: 1, 2.8: 1, 3: 1 or any value therebetween. In a preferred embodiment, oil phase lubricant is a mixture of paraffin and fatty acid and white vaseline, now possesses softened paraffin and abundant lubricity advantages, can effectively reduce grinding cutting force to ensure thermal stability, is more conducive to the feedback of metallographic structure authenticity. Further, the mass ratio of paraffin, fatty acid and white vaseline in the oil phase lubricant is preferably (2.0-2.3):(0.2-0.5):1, such as 2:0.2:1, 2:0.3:1, 2:0.4:1, 2:0.5:1, 2.1:0.2:1, 2.1:0.3:1, 2.1:0.4:1, 2.1:0.5:1, 2.2:0.2:1, 2.2:0.3:1, 2.2:0.4:1, 2.2:0.5:1, etc. Specific examples of fatty acids include, but are not limited to, at least one of palmitic acid, oleic acid, linoleic acid, linolenic acid, palmitic acid, behenic acid, lauric acid, and animal and vegetable oils.
[0032] In the present invention, the mass ratio of solid polyethylene glycol and small molecule polyol in the aqueous lubricant is preferably 1: (1-1.5), such as 1: 1, 1: 1.2, 1: 1.4, 1: 1.5 or any value therebetween. Wherein, specific examples of solid polyethylene glycol include but are not limited to at least one of PEG-1500, PEG-2000, PEG-3000 and PEG-4000. Small molecule polyol is preferably selected from at least one of glycerol, propylene glycol and ethylene glycol. The use of solid polyethylene glycol can effectively clean the dirt and grease on the surface of cemented carbide, enhance the cleaning effect of the grinding paste, and improve the decontamination ability. The use of small molecule polyol can prevent the lubricating main material from crystallizing and hardening again, while increasing the viscosity of the paste and promoting the dispersion and fusion of the lubricating main material with other additives.
[0033] In the present invention, the emulsifier is preferably a mixture of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters and oleic acid. The mass ratio of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters and oleic acid in the emulsifier is preferably (0.3-0.5): (0.5-0.8): 3, such as 0.3: 0.5: 3, 0.3: 0.6: 3, 0.3: 0.8: 3, 0.4: 0.5: 3, 0.4: 0.6: 3, 0.4: 0.8: 3, 0.5: 0.5: 3, 0.5: 0.6: 3, 0.5: 0.8: 3 or any value therebetween. Mono- and di-glycerol fatty acid esters include mono- and di-glycerol fatty acid esters. Wherein, mono- and di-glycerol fatty acid esters are composed of one glycerol molecule and one fatty acid molecule, while di-glycerol fatty acid esters are composed of two glycerol molecules and one fatty acid molecule. Specific examples of mono- and di-glycerol fatty acid esters include, but are not limited to, at least one of the composite emulsifiers such as di-glycerol fatty acid esters, propylene glycol fatty acid esters, and polyglycerol fatty acid esters. Specific examples of sorbitol fatty acid esters include, but are not limited to, at least one of the Span series, Tween series, and fatty alcohol polyoxyethylene ethers. The use of mono- and di-glycerol fatty acid esters and sorbitol fatty acid esters can promote the fine and uniform fat particles in the grinding paste and promote the uniform mixing of immiscible bodies. The use of oleic acid has both hydrophilic and lipophilic groups, which can achieve mutual stability between oil and water. The composite addition of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters, and oleic acid can effectively promote the uniform mixing of oil and water lubricants, prevent the occurrence of grease stratification, avoid the occurrence of metallographic structure distortion caused by excessive heating of cemented carbide bonding phase structure grinding, and facilitate sample cleaning.
[0034] In the present invention, polyvinyl pyrrolidone is used to adjust the particle size of stearates such as paraffin wax in the paste during the hot melting and cooling process, so as to make the paste more delicate and uniform and promote the dispersion of various ingredients in the paste.
[0035] In the present invention, the dispersant is preferably a mixture of liquid polyethylene glycol, polyvinyl alcohol and pure water. The mass ratio of liquid polyethylene glycol, polyvinyl alcohol and pure water in the dispersant is preferably (2-4): (0.5-1): 5, such as 2: 0.5: 5, 2: 0.6: 5, 2: 0.8: 5, 2: 1: 5, 3: 0.5: 5, 3: 0.6: 5, 3: 0.8: 5, 3: 1: 5, 4: 0.5: 5, 4: 0.6: 5, 4: 0.8: 5, 4: 1: 5, etc. The polyvinyl alcohol aqueous suspension can be used as a carrier of nano-diamond abrasive to promote the dispersion of diamond powder. Liquid polyethylene glycol is preferably PEG-400. The use of liquid polyethylene glycol can form a protective film on the surface of diamond powder to prevent the diamond powder from aggregating again and affecting the uneven cutting and causing metallographic structure distortion.
[0036] The grinding paste provided by the present invention can be used alone, or dissolved in liquid oil to form an oily grinding paste or grinding liquid, or dissolved in water to form a water-soluble grinding paste or grinding liquid. The grinding paste has the advantages of both oil and water lubricants, and can effectively solve the problems of excessive grinding heat and subsequent cleaning.
[0037] The preparation method of the grinding paste provided by the present invention comprises uniformly mixing abrasive, oil phase lubricant, water phase lubricant, emulsifier, polyvinyl pyrrolidone and optional dispersant. The present invention has no particular limitation on the uniform mixing method. The components can be added in any order and then mixed. Preferably, the uniform mixing method comprises: S1. Stirring and mixing the abrasive and dispersant, and then ultrasonically dispersing them in an ultrasonic machine for 10-15 minutes, stirring continuously during the ultrasonic dispersion process to obtain a liquid paste; S2. Stirring and mixing the oil phase lubricant, water phase lubricant, emulsifier and polyvinyl pyrrolidone at 70-90°C until the components are liquefied, adding the liquid paste and continuously keeping warm and stirring at 50-60°C for 10-20 minutes to promote the emulsification of the paste, and then naturally cooling and stirring to room temperature to obtain a premixed paste; S3. Filtering the premixed paste to remove a small amount of recrystallized bodies to obtain the grinding paste. In step S3, the purpose of filtering is to remove a small amount of coarse recrystallized bodies generated during the paste processing, so that the paste is more uniform and delicate. The pore size of the sieve used for filtration is preferably 50-100 mesh, such as 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh or any value therebetween.
[0038] The invention also provides application of the grinding paste in hard alloy polishing.
[0039] The present invention will be described in detail below through examples.
[0040] In the following examples and comparative examples, paraffin wax was purchased from PetroChina Co., Ltd. with a brand name of 58#; polyethylene glycol was purchased from Guangdong Nanhui New Materials Co., Ltd. with models of PEG-400 and PEG-1500; mono- and di-glycerol fatty acid esters were purchased from Jialishi Additives (Haian) Co., Ltd., oleic acid glyceride, 99% distilled grade; sorbitol fatty acid esters were purchased from Guangdong Runhua Chemical Co., Ltd. with a brand name of S-80; polyvinyl alcohol was purchased from Sinopec Shanghai Petrochemical Co., Ltd. with a model name of PVA 2099.
[0041] Example 1 Abrasive paste and preparation method thereof
[0042] S1. The abrasive and the dispersant were stirred and mixed uniformly, and then ultrasonically dispersed in an ultrasonic machine for 15 minutes, and stirring was continued during the ultrasonic dispersion process to obtain a liquid paste;
[0043] S2. Put the oil phase lubricant, water phase lubricant, emulsifier and polyvinyl pyrrolidone into a stirrer, heat to 80°C and stir until all components are liquefied, then add the liquid paste and keep stirring at 60°C for 15 minutes to emulsify the paste, then naturally cool and stir to room temperature to obtain a premixed paste;
[0044] S3. Filter the premixed paste through a sieve with a pore size of 80 mesh to obtain the grinding paste.
[0045] The abrasive is diamond micropowder with a particle size of 0.5-1.5 microns. The oil phase lubricant is a mixture of paraffin, palmitic acid and white vaseline in a mass ratio of 2:0.5:1. The water phase lubricant is a mixture of PEG-1500 and propylene glycol in a mass ratio of 1:1.2. The emulsifier is a mixture of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters and oleic acid in a mass ratio of 0.4:0.6:3. The dispersant is a mixture of PEG-400, polyvinyl alcohol and purified water in a mass ratio of 3:0.8:5. The amount of each component is shown in Table 1.
[0046] Example 2 Abrasive paste and preparation method thereof
[0047] S1. The abrasive and the dispersant were stirred and mixed uniformly, and then ultrasonically dispersed in an ultrasonic machine for 15 minutes, and stirring was continued during the ultrasonic dispersion process to obtain a liquid paste;
[0048] S2. Put the oil phase lubricant, water phase lubricant, emulsifier and polyvinyl pyrrolidone into a stirrer, heat to 70°C and stir until all components are liquefied, then add the liquid paste and keep stirring at 50°C for 10 minutes to emulsify the paste, then naturally cool and stir to room temperature to obtain a premixed paste;
[0049] S3. Filter the premixed paste through a sieve with a pore size of 80 mesh to obtain the grinding paste.
[0050] The abrasive is diamond micropowder with a particle size of 0.5-1.5 microns. The oil phase lubricant is a mixture of paraffin, palmitic acid and white vaseline in a mass ratio of 2:0.5:1. The water phase lubricant is a mixture of PEG-1500 and glycerol in a mass ratio of 1:1.2. The emulsifier is a mixture of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters and oleic acid in a mass ratio of 0.4:0.6:3. The dispersant is a mixture of PEG-400, polyvinyl alcohol and purified water in a mass ratio of 3:0.8:5. The amount of each component is shown in Table 1.
[0051] Example 3 Abrasive paste and preparation method thereof
[0052] S1. The abrasive and the dispersant were stirred and mixed uniformly, and then ultrasonically dispersed in an ultrasonic machine for 15 minutes, and stirring was continued during the ultrasonic dispersion process to obtain a liquid paste;
[0053] S2. Put the oil phase lubricant, water phase lubricant, emulsifier and polyvinyl pyrrolidone into a stirrer, heat to 90°C and stir until all components are liquefied, then add the liquid paste and keep stirring at 50°C for 20 minutes to emulsify the paste, then naturally cool and stir to room temperature to obtain a premixed paste;
[0054] S3. Filter the premixed paste through a sieve with a pore size of 80 mesh to obtain the grinding paste.
[0055] The abrasive is diamond micropowder with a particle size of 2-2.5 microns. The oil phase lubricant is a mixture of paraffin, lauric acid and white vaseline in a mass ratio of 2:0.5:1. The water phase lubricant is a mixture of PEG-1500 and ethylene glycol in a mass ratio of 1:1.2. The emulsifier is a mixture of mono- and di-glycerol fatty acid esters, sorbitol fatty acid esters and oleic acid in a mass ratio of 0.4:0.6:3. The dispersant is a mixture of PEG-400, polyvinyl alcohol and purified water in a mass ratio of 3:0.8:5. The amount of each component is shown in Table 1.
[0056] Example 4 Abrasive paste and preparation method thereof
[0057] The grinding paste was prepared according to the method of Example 1, except that the particle size of the diamond powder was controlled to be 3-3.5 μm, and the other conditions were the same as those of Example 1 to obtain the grinding paste. The amount of each component used is shown in Table 1.
[0058] Example 5 Abrasive paste and preparation method thereof
[0059] The grinding paste was prepared according to the method of Example 1, except that the oleic acid in the emulsifier was replaced by the same weight of mono- and di-glycerol fatty acid esters, and the other conditions were the same as in Example 1 to obtain the grinding paste. The amount of each component is shown in Table 1.
[0060] Example 6 Abrasive paste and preparation method thereof
[0061] The grinding paste was prepared according to the method of Example 1, except that the mono- and di-glycerol fatty acid esters in the emulsifier were replaced with sorbitol fatty acid esters in the same weight parts, and the other conditions were the same as those of Example 1 to obtain the grinding paste. The amount of each component used is shown in Table 1.
[0062] Example 7 Abrasive paste and preparation method thereof
[0063] The grinding paste was prepared according to the method of Example 1, except that the dispersant was replaced by the same weight portion of the emulsifier to obtain the grinding paste. The amount of each component used is shown in Table 1.
[0064] Example 8 Abrasive paste and preparation method thereof
[0065] The grinding paste was prepared according to the method of Example 1, except that the paraffin wax and palmitic acid in the oil phase lubricant were replaced by white vaseline in equal parts by weight, and the other conditions were the same as those of Example 1 to obtain the grinding paste. The amounts of the components used are shown in Table 1.
[0066] Comparative Example 1 Reference grinding paste and preparation method thereof
[0067] A grinding paste was prepared according to the method of Example 1, except that the oil phase lubricant was replaced by the same weight portion of the water phase lubricant, and the other conditions were the same as in Example 1 to obtain a reference grinding paste. The amount of each component is shown in Table 1.
[0068] Comparative Example 2 Reference grinding paste and preparation method thereof
[0069] A grinding paste was prepared according to the method of Example 1, except that the water phase lubricant was replaced by the same weight portion of the oil phase lubricant, and the other conditions were the same as in Example 1 to obtain a reference grinding paste. The amount of each component is shown in Table 1.
[0070] Comparative Example 3 Reference grinding paste and preparation method thereof
[0071] A grinding paste was prepared according to the method of Example 1, except that polyvinyl pyrrolidone was replaced by a dispersant of the same weight portion to obtain a reference grinding paste. The amount of each component used is shown in Table 1.
[0072] Table 1
[0073]
[0074]
[0075] Test Case
[0076] The grinding paste obtained in the above embodiments and the reference grinding paste obtained in the comparative example were used to perform grinding and polishing tests on the metallographic surfaces of coarse and fine-grained cemented carbide materials. The specific process and conditions are as follows: the test grinding process was carried out on the same automatic polishing machine with an upper disk speed of 3.5 rpm and a lower disk speed of 400 rpm; the polishing cloth was a long-pile fabric polishing cloth; the amount of grinding paste was evenly applied at 1.5 g / time; and the grinding and polishing time was 3 minutes for testing. The microscopic metallographic effects before and / or after polishing are shown in Table 2. The microscopic metallographic effect diagrams (X100) before and after polishing using the grinding paste obtained in Examples 1-3 are shown in Table 2. Figure 1-Figure 6 The microscopic metallographic effect diagrams (X100) after polishing of the abrasive pastes obtained in Examples 4-8 and Comparative Examples 1-3 are shown in FIG. Figure 7-Figure 14 .
[0077] Table 2
[0078]
[0079]
[0080] From Table 2 and Figure 1-Figure 14 It can be seen from the results that the polishing of cemented carbide by the abrasive paste provided by the present invention can not only well avoid the residue of oily substances, but also effectively avoid the occurrence of metallographic structure distortion, so that it meets the requirements of metallographic observation.
[0081] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A grinding paste, characterized in that: The grinding paste contains abrasive, oil phase lubricant, water phase lubricant, emulsifier and polyvinyl pyrrolidone and optional dispersant in a mass ratio of 100:(300-1000):(300-1000):(100-600):(10-160):(0-300); the oil phase lubricant is white vaseline or a mixture of paraffin and / or fatty acid and white vaseline; the water phase lubricant is a mixture of solid polyethylene glycol and small molecule polyol.
2. The abrasive paste according to claim 1, characterized in that The content of the abrasive is 5-10 parts by weight, the content of the oil phase lubricant is 30-50 parts by weight, the content of the water phase lubricant is 30-50 parts by weight, the content of the emulsifier is 10-30 parts by weight, the content of the polyvinyl pyrrolidone is 1-8 parts by weight, and the content of the dispersant is 5-15 parts by weight.
3. The abrasive paste according to claim 1, characterized in that The abrasive is diamond powder; the particle size of the diamond powder is 0.5-2.5 microns, preferably 0.5-1.5 microns.
4. The abrasive paste according to claim 1, characterized in that When the oil phase lubricant is a mixture of paraffin and / or fatty acids and white vaseline, the mass ratio of the total content of paraffin and fatty acids in the oil phase lubricant to the content of white vaseline is (2-3):1; preferably, the oil phase lubricant is a mixture of paraffin, fatty acids and white vaseline; preferably, the mass ratio of paraffin, fatty acids and white vaseline in the oil phase lubricant is (2.0-2.3):(0.2-0.5):1; preferably, the fatty acid is selected from at least one of palmitic acid, oleic acid, linoleic acid, linolenic acid, palmitic acid, behenic acid, lauric acid and animal and vegetable oils.
5. The abrasive paste according to claim 1, characterized in that The mass ratio of solid polyethylene glycol to small molecule polyol in the water-phase lubricant is 1:(1-1.5); preferably, the solid polyethylene glycol is selected from at least one of PEG-1500, PEG-2000, PEG-3000 and PEG-4000; preferably, the small molecule polyol is selected from at least one of glycerol, propylene glycol and ethylene glycol.
6. The abrasive paste according to claim 1, characterized in that The emulsifier is a mixture of mono- and di-glycerol fatty acid esters, sorbitan fatty acid esters and oleic acid; preferably, the mass ratio of mono- and di-glycerol fatty acid esters, sorbitan fatty acid esters and oleic acid in the emulsifier is (0.3-0.5):(0.5-0.8):
3.
7. The abrasive paste according to claim 1, characterized in that The dispersant is a mixture of liquid polyethylene glycol, polyvinyl alcohol and purified water; preferably, the mass ratio of liquid polyethylene glycol, polyvinyl alcohol and purified water in the dispersant is (2-4):(0.5-1):5; preferably, the liquid polyethylene glycol is PEG-400.
8. The method for preparing the abrasive paste according to any one of claims 1 to 7, characterized in that: The method comprises uniformly mixing abrasive, oil phase lubricant, water phase lubricant, emulsifier, polyvinyl pyrrolidone and optional dispersant.
9. The method for preparing the abrasive paste according to claim 8, characterized in that: The uniform mixing method comprises: S1. The abrasive and the dispersant are stirred and mixed, and then ultrasonically dispersed in an ultrasonic machine for 10-15 minutes, and the ultrasonic dispersion process is continuously stirred to obtain a liquid paste; S2. The oil phase lubricant, the water phase lubricant, the emulsifier and the polyvinyl pyrrolidone are stirred and mixed at 70-90°C until the components are liquefied, the liquid paste is added and the paste is continuously stirred at 50-60°C for 10-20min to promote the emulsification of the paste, and then naturally cooled and stirred to room temperature to obtain a premixed paste; S3. Filter the premixed paste to remove a small amount of recrystallized solids to obtain the grinding paste.
10. Use of the abrasive paste according to any one of claims 1 to 7 in polishing hard alloys.
